2011
DOI: 10.1097/nna.0b013e31820c7258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Outsourced Nursing on Quality Outcomes in Long-term Acute-Care Hospitals

Abstract: Use of outsourced nurses is often a stop-gap measure for unplanned vacancies in smaller healthcare facilities such as long-term acute-care hospitals (LTACHs). However, the relationship of utilization levels (low, medium, or high percentages) of nonemployees covering staff schedules often is perceived to have negative relationships with quality outcomes. To assess this issue, the authors discuss the outcomes of their national study of LTACH hospitals that indicated no relationship existed between variations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…6,7 Additionally, several studies included RNs, LPNs, and unlicensed assistive personnel (UAP) in their analysis. For instance, one study evaluated the utilization level (low, medium, high variations in staffing levels) of outsourced nurses in long-term acute hospitals, whereas another study used the hours of care provided by external temporary nurses.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 Additionally, several studies included RNs, LPNs, and unlicensed assistive personnel (UAP) in their analysis. For instance, one study evaluated the utilization level (low, medium, high variations in staffing levels) of outsourced nurses in long-term acute hospitals, whereas another study used the hours of care provided by external temporary nurses.…”
Section: Methodsmentioning
confidence: 99%
“…Bae et al (2014) found the association between temporary nursing staff and BSI and ventilator-associated pneumonia was not significant. Alvarez et al (2011) did not find a relationship between CAUTI and travel nurse staffing. Faller et al (2017) also found CAUTIs were not related to travel nurse rates though they reported a significant association between BSIs and travel nurse rates in two out of five nursing units.…”
Section: Outcome Variablesmentioning
confidence: 58%
“…Of the eight studies investigating medication errors, most (5, 63%) did not observe a significant association, whereas two (25%) reported beneficial relationships and one (13%) reported an adverse association with travel nurses. Alvarez et al (2011), Breckenridge-Sproat et al ( 2012), Hart and Davis (2011), Patrician et al (2011), andXue et al (2012) did not observe any significant association between travel nurses and medication errors. Conversely, Aiken et al (2007) and Bae et al (2010) suggest an improvement in medication errors associated with travel nurse usage.…”
Section: Outcome Variablesmentioning
confidence: 88%
See 1 more Smart Citation
“…There was no difference in quality of care, but EBP was not examined directly in this study. 12 Respondents who scored higher on the knowledge subscale had increased scores on the EBP practice subscale. This may be a starting place for EBP interventions to increase overall adoption.…”
Section: Discussionmentioning
confidence: 97%